2014
DOI: 10.1016/j.rasd.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Internal state language in the storybook narratives of children with and without autism spectrum disorder: Investigating relations to theory of mind abilities

Abstract: The current study examines narratives elicited using a wordless picture book, focusing on language used to describe the characters’ thoughts and emotions (i.e., internal state language, ISL). The sample includes 21 children with Autism Spectrum Disorder (ASD) and 24 typically developing controls, matched on children's gender, IQ, as well as receptive and expressive vocabulary. This research had three major findings. First, despite equivalent performance on standardized language assessments, the volume of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 37 publications
3
51
1
4
Order By: Relevance
“…We found significant differences according to diagnostic group (TD > HFASD), but not gender, on the total number of emotion terms in spontaneous narrative, similar to previous research (Perlman-Avnion and Eviatar 2002;Sillar et al 2014). However, a female advantage in this task would be predicted from TD population studies (Thompson and Moore 2000;Newman et al 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found significant differences according to diagnostic group (TD > HFASD), but not gender, on the total number of emotion terms in spontaneous narrative, similar to previous research (Perlman-Avnion and Eviatar 2002;Sillar et al 2014). However, a female advantage in this task would be predicted from TD population studies (Thompson and Moore 2000;Newman et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…For example, one implication of using fewer causal markers at the above-sentence level might be impoverished sequencing of related information in narrative and discourse. Poor sequencing of narrative information will directly impact on conveying a point of view (Sillar et al 2014), which will in turn impact on the individual's ability to self-advocate. In addition, a narrower range of vocabulary choices in connected speech will also mark the speaker as less skilled than her peers and subtly less linguistically mature.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Losh and Capps (2003) found that autistic children's use of mental state terms in personal and storybook narratives (cognitive or affective) were significantly associated with their ability to define emotions, but not to ToM abilities. Recent work (Siller, Swanson, Serlin, & Teachworth, 2014) showed that autistic children's general ToM scores were related to their use of emotion terms during a wordless picture book interaction, but not to their use of cognition terms.…”
mentioning
confidence: 99%
“…In contrast, Losh and Capps [47] found that autistic children's use of mental state terms in personal and storybook narratives (cognitive or affective) were significantly associated with their ability to define emotions, but not to ToM abilities. Recent work [50] showed that autistic children's general ToM scores were related to their use of emotion terms during a wordless picture book interaction, but not to their use of cognition terms. Differences across studies might have to do with context effects on internal state talk.…”
Section: Early Explicit Tom In Spontaneous Mental State Languagementioning
confidence: 99%